Fe and Zr/Rb XRF data from Black Sea sediment core M72/5-22GC-8 during Termination 2 - Markus Czymzik; Marcus Christl; Helge Wolfgang Arz (PANGAEA, 2025)
Fe and Zr/Rb records spanning Termination 2 were obtained from Black Sea sediment core M72/5-22GC-8 (803.75 -941.75 cm core depth) at 500 μm resolution using an ITRAX core scanner equipped with a Cr tube at 30 kV, 30 mA and with 15 seconds dwell time in 2020. Sediment core M72/5-22GC-8 was recovered from the south-eastern Black Sea (Archangelsky Ridge, 42°13.5 extquotesingleN, 36°29.6 extquotesingleE, 847 m bsl.) using a gravity corer during RV Meteor cruise M72/5 in 2007. Primary objective of the measurements was to establish time-series of multi-decadal element variability.